2002
DOI: 10.1029/2000jc000498
|View full text |Cite
|
Sign up to set email alerts
|

Observations of surf beat forcing and dissipation

Abstract: [1] We used a simple energy balance equation, and estimates of the cross-shore energy flux carried by progressive surf beat, to calculate the rate of net surf beat forcing (or dissipation) on a beach near Duck, North Carolina. Far inside the surf zone, surf beat dissipation exceeded forcing. Outside the surf zone, surf beat forcing exceeded dissipation. When incident waves were large, surf beat dissipation inside the surf zone and forcing just outside the surf zone were both very strong (the surf beat energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 63 publications
(99 reference statements)
5
105
1
Order By: Relevance
“…In water depths less than about 1 m, φ > 0 and infragravity energy is lost to higher Although tidal modulations were absent, previous studies on the North Carolina coast [Henderson and Bowen, 2002] identified similar cross-shore regions and rates of net infragravity gain and loss, and suggested that bottom drag may account for the observed losses, even though the drag coefficient necessary to explain the observations was an order of magnitude larger than estimates from other published studies of the nearshore region. Equation (2.2) neglects bottom drag, and instead demonstrates that nonlinear energy exchanges between infragravity waves and higher frequencies (swell and wind waves) explain most of the infragravity losses, similar to a concurrent study on the North Carolina coast [Henderson et al, submitted, 2006].…”
Section: Nonlinear Energy Balancecontrasting
confidence: 47%
See 1 more Smart Citation
“…In water depths less than about 1 m, φ > 0 and infragravity energy is lost to higher Although tidal modulations were absent, previous studies on the North Carolina coast [Henderson and Bowen, 2002] identified similar cross-shore regions and rates of net infragravity gain and loss, and suggested that bottom drag may account for the observed losses, even though the drag coefficient necessary to explain the observations was an order of magnitude larger than estimates from other published studies of the nearshore region. Equation (2.2) neglects bottom drag, and instead demonstrates that nonlinear energy exchanges between infragravity waves and higher frequencies (swell and wind waves) explain most of the infragravity losses, similar to a concurrent study on the North Carolina coast [Henderson et al, submitted, 2006].…”
Section: Nonlinear Energy Balancecontrasting
confidence: 47%
“…Previous studies have attributed infragravity energy loss to bottom drag [Raubenheimer et al, 1995, Henderson andBowen, 2002] and to breaking .…”
Section: Introductionmentioning
confidence: 99%
“…The amplitude of the reflected negative pulse is smaller than that of the incident bound wave trough in the inner surf zone. The process of reduction of the negative pulse appears to be linked to the superposition of long waves generated within the surf and the swash zone (Baldock 2006) rather than to the dissipation owing to bottom friction (Henderson & Bowen 2002). Therefore, the presence of the outgoing positive pulse which propagates from the shoreline at t ≈ 115 s can be explained as a low-frequency wave generated within the surf and swash zone.…”
Section: (B) Evolution Of the Low-frequency Componentmentioning
confidence: 99%
“…The flowmeters were sampled at a rate of 2 Hz in half hour intervals continuously. Further details on the instrumentation are given by Henderson and Bowen [2002] and Hay and Mudge [2005].…”
Section: Field Site and Datamentioning
confidence: 99%